1988
DOI: 10.1111/j.1523-536x.1988.tb00807.x
|View full text |Cite
|
Sign up to set email alerts
|

Psychologic, Physical, Nutritional, and Technologic Aspects of Intravenous Infusion During Labor

Abstract: Giving intravenous (IV) fluids in labor is currently an accepted custom in United States hospitals, although most indications for this practice have not been validated by adequate outcome research. This paper discusses the following questions: I) Does IV therapy add pain to the woman in labor? 2) Does it have an adverse impact on the attitudes of health care workers and on the laboring woman? 3) Does partial immobilization caused by IV lines have adverse effects? 4) Does the practice introduce a possible route… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0

Year Published

1991
1991
2000
2000

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 26 publications
0
11
0
Order By: Relevance
“…Adverse psychological effects of IVH were reviewed by Newton et al (24). They noted that not only did the IV apparatus itself cause pain, but that it could increase the perception of pain by laboring women, especially if large, rapid injections of glucose were given.…”
Section: Review Of the Literaturementioning
confidence: 99%
“…Adverse psychological effects of IVH were reviewed by Newton et al (24). They noted that not only did the IV apparatus itself cause pain, but that it could increase the perception of pain by laboring women, especially if large, rapid injections of glucose were given.…”
Section: Review Of the Literaturementioning
confidence: 99%
“…It is well-known, however, that throughout pregnancy, women accumulate stores of extra fat and fluids. According to Newton, Newton, and Broach (1988), normal, healthy women at term have at least two liters of water stored in their extravascular spaces. At the same time that fasting in labor became the standard, intravenous infusions also became routine for laboring women in the United States.…”
Section: Intravenous Hydration In Labormentioning
confidence: 99%
“…One liter of 5% dextrose in water or salt solution provides only 225 calories. Routine use of IV fluids may have adverse side effects on maternal well‐being (fluid overload, discomfort, and decreased mobility) and fetal/newborn well‐being (hyponatremia, hyper‐ and subsequent hypoglycemia) (19,20,22,23).…”
Section: Energy Utilizationmentioning
confidence: 99%
“…In addition to providing hydration, nutrition, and comfort, self‐regulating intake decreases a women's stress level and provides her with a feeling of control (22). Penny Simpkin assessed stressful childbirth events and found that 27% of women considered restriction of food in labor “moderately” to “most” stressful; 57% found restriction of fluids to be “moderately” to “most” stressful (27).…”
Section: Stressmentioning
confidence: 99%